A new Mexican species and new taxonomic and distributional data of Strigoderma Burmeister (Coleoptera: Scarabaeidae: Rutelinae) - Delgado, Leonardo; Mora-Aguilar, Eder F. (Zootaxa, 2012)
A new species of scarab beetle, Strigoderma tenebrosa new species, is described from the state of Chiapas, Mexico. The new species belongs to the S. costulipennis species group, and a new key to this group is presented in order to facilitate the identification of this species. Taxonomic comments and new distributional data are given for S. contracta Bates, S. costulata Nonfried, S. festiva Bates, S. longicollis Bates, S. presidii Bates, S. protea Burmeister, and S. teapensis Bates.